The Effect of the Mere Exposure Effect on Language Teaching and Learning - Fakhoury, Raneen Khaleel; Farrah, Mohammed (LinguaEducare: Journal of English and Linguistic Studies, 2025)
This research paper is trying to answer the question “What is the effect of the mere exposure effect on language teaching and learning?” In order to answer this question, the researcher analyzed both the process of the mere exposure effect and a number of previous studies about the subject. The mere exposure effect is the increased favorability of a specific stimulus due to repeated exposure to said stimulus. The results of this research paper show that the mere exposure effect can have both a positive effect and a negative effect on language teaching and learning. However, these effects depend on the existence or non-existence of certain factors alongside the mere exposure effect. In the case of the mere exposure effect having a positive effect on language teaching and learning, several factors must exist alongside it. These factors include varied and new subjects, varied styles of teaching and learning, adaptability, and a love for languages. This shows that the mere exposure effect is only a factor in the processes of language teaching and learning. So, teachers and students must pay attention to the other factors and not only to the mere exposure effect in order to achieve a positive effect on language teaching and learning.